Retailers' Preferences In Choosing Wholesalers In Paringin, South Kalimantan - Muhammad Qamaruddin; Akhmad Madani; fathurrahman Azhari (IAIN Kendari, 2022)
The background of this research is that there are differences in retailers' preferences in choosing wholesalers in Paringin, South Kalimantan. This study aims to determine the factors that influence retailers' preferences in choosing wholesalers. This research is a qualitative approach using observation, interviews, and documentation. Then, the data is analyzed by descriptive analysis techniques qualitative. The results of the study found factors that influence the preferences of retailers in choosing wholesalers are: 1) Easily accessible location, 2) complete item, 3) item availability, 4) getting item practically, 5) Long opening time, 6) Price, 7) speed of service, and 8) goods benefits.